KESADARAN DAN KECERDASAN SPIRITULITAS - Rahman, Fathur (Tasamuh: Jurnal Studi Islam, 2017)
Spiritual intelligence is the internal factors that can affect a personâs mental high and low resistance. The spiritual intelligence is the ability of character and positive character. Spiritual intelligence is useful, because it enables people to realize who the real man and how people give meaning to life. The spiritual intelligence as a trigger for human to do everything that related with human values. Thus, there is a relationship between ownership spiritual intelligence and mental endurance. Someone who has a spiritual intelligence have low mental endurance is low. Low mental endurance, they indicated a potential for inappropriate behavior. Not to perform deviant behavior, then someone needs to find true happiness. They require a search for meaning, vision and value of life becomes an important aspect of human existence, (The search for meaning, vision and value is the most important aspect of being human). Although the spiritual is not identical with religiosity (religiosity), but spiritual intelligence as a human guide in life can be achieved through awareness and appreciation of true religiousness. This is to encourage people to do more humane, so it can reach the noble values that may not have been touched by the mind. Consciousness is aware of us holistically. That awareness includes awareness of human existence in the presence of the creator of universe, human beings and other creatures, awareness of human potential, awareness of human weakness that human life requires illahiyyah instructions.